Scenario Planning for Resilient Agricultural Systems: A Process for Engaging Controversy - Crystal A. Powers; Tyler Williams; Rick R. Stowell ([TEST] Journal of Extension, 2021)
Resiliency to weather extremes is already a part of farming in the North Plains, but now climate change is adding new uncertainties. Engaging farmers on this often controversial topic can be challenging given the wide range of beliefs farmers hold about climate change. Scenario planning provides a framework for Extension and agricultural system stakeholders to come together using the latest climate science to discover robust adaptive management options, prioritize Extension programming needs, and provide an open forum for starting the discussion.
Keywords: Climate Change; scenario planning; needs assessment